The making of a Mediterranean emirate Ifrīqiyā and its Andalusis, 1200-1400 - Rouighi, Ramzi (Middle Ages series, 2011)
This book argues that between 1200 and 1400 Ifrīqiya was not an economic or political region. It shows how Emirism, a political ideology that emerged at the end of the fourteenth century, led both medieval sources and modern historians to imagine Ifrīqiya as a region